Digestibility and Bioaccessibility of Pickering Emulsions of Roasted Coffee Oil Stabilized by Chitosan and Chitosan-Sodium Tripolyphosphate Nanoparticles - Ribeiro, Elisa Franco [UNESP]; Borreani, Jennifer; Moraga, Gemma; Nicoletti, Vânia Regina [UNESP]; Quiles, Amparo; Hernando, Isabel (Springer Nature, 2020)
Due to the valuable lipid fraction composition present in roasted coffee oil, it has become important to develop methods that modify its structure, such as emulsion-based encapsulation systems, favoring its use in food industry. Pickering emulsions have appeared as a potential alternative to protect oil droplets stabilized by solid particles rather than the use of surfactants. This work investigated the ability of chitosan (CS) nanoparticles produced by deprotonation and by ionic gelation to stabilize emulsions with different lipid phase content as an alternative to encapsulate roasted coffee oil. An in vitro digestion model consisting of mouth, gastric and intestinal phases was used to characterize the rate and extent of lipid phase digestion, emulsion microstructure, and bioaccessibility of total phenolic compounds. All emulsions presented some structural changes attributed to flocculation and coalescence throughout simulated gastrointestinal digestion. Better droplet stabilization using the deprotonation method was achieved when lower oil content was used, leading to higher bioaccessibility of total phenolic compounds.
Keywords: Delivery systems; Encapsulation; Functional foods; Microstructure; Phenolic compounds